A Novel Multi‐step Virtual Screening for the Identification of Human and Mouse mPGES‐1 Inhibitors. Issue 8 (23rd May 2016) - Corso, G.; Alisi, M. A.; Cazzolla, N.; Coletta, I.; Furlotti, G.; Garofalo, B.; Mangano, G.; Mancini, F.; Vitiello, M.; Ombrato, Rosella
Abstract: We present here the development of a novel virtual screening protocol combining Structure‐based and Ligand‐based drug design approaches for the identification of mouse mPGES‐1 inhibitors. We used the existing1 3D structural data of the murine enzyme to hypothesize the inhibitors binding mode, which was the starting point for docking simulations, shape screening, and pharmacophore hypothesis screening. The protocol allowed the identification of 16  mouse mPGES‐1 inhibitors with low micromolar activity, which, notably, also inhibit the human enzyme in the same concentration range. The inhibitors predicted binding mode is expected to be the base for the rational drug design of new potent dual species inhibitors of human and murine mPGES‐1. Abstract :